Synopsis of biological, ecological and fisheries-related information on priority marine species in the Azores region - Santos, Régis (2021)
Studies on life history and stock structure of marine species have evolved in the Azores region during the last 40 years. This information is essential to feed fishery stock assessment models that fit available data to determine current stock status and provide advice on the optimum (sustainable) exploitation. However, most of these data are only available in a fragmented manner in several scientific papers, books, theses and reports. In some cases, these sources of information are difficult to access. The present document aims to gather and summarize biological, ecological and fisheries-related information for the main commercially exploited species in the Azores. The species treated here have previously been selected as priority stocks for assessment and monitoring at regional level by applying a standard framework aligned with the ICES and FAO recommendations. They are: the blackspot seabream Pagellus bogaraveo, veined squid Loligo forbesii, blue jack mackerel Trachurus picturatus, blackbelly rosefish Helicolenus dactylopterus, red porgy Pagrus pagrus, forkbeard Phycis phycis, European conger Conger conger, alfonsino Beryx decadactylus, splendid alfonsino B. splendens, parrotfish Sparisoma cretense, silver scabbardfish Lepidopus caudatus, red scorpionfish Scorpaena scrofa, Atlantic chub mackerel Scomber colias, blacktail comber Serranus atricauda, offshore rockfish Pontinus kuhlii, amberjacks nei Seriola spp., common mora Mora moro, common spiny lobster Palinurus elephas, black scabbardfish Aphanopus carbo, rough limpet Patella aspera, thornback ray Raja clavata, and Mediterranean slipper lobster Scyllarides latus. The document is presented as concisely and effectively as possible. An overview table of the current data available is presented by stock.